Sistem Informasi Penjualan Berbasis WEB Pada UKM Rukun Makmur Tlingsing - Umi Khultsum; F. LIa Dwi Cahyanti; Elly Firasari (NUANSA INFORMATIKA, 2024)
In today's globalized era, rapid advancements in information systems have had a profound impact on business operations. UKM Rukun Makmur, based in Tlingsing Village, Cawas District, Klaten Regency, specializes in producing woven lurik fabric and faces several challenges. These include limited traditional marketing methods such as brochures and catalogs, which restrict sales efficiency and outreach. Additionally, there is a lack of staff familiarity with internet tools, hindering business growth. The use of traditional weaving equipment also limits production capacity. Insufficient digital marketing efforts have resulted in low brand visibility and below-target sales revenue for this SME. Thus, it is essential to develop a web-based sales information system for UKM Rukun Makmur Tlingsing to expand product marketing reach and boost sales. This system will be built using the waterfall methodology, encompassing phases such as requirements analysis, design, implementation, and testing. Open-source tools like XAMPP, MySQL, and PHP will be employed, ensuring accessibility for all users